Semântica e pragmática: duas formas de descrever e explicar os fenômenos da significação (Revista de Estudos da Linguagem, 2000)
The boundaries between Semantics and Pragmatics still deserve to beinvestigated, since they remain unclear for many linguists, and since theword “pragmatics” has quite often been used among Brazilian linguists inan unscientific, rhetorical way, to enhance the importance of some approachesto meaning and interpretation.This paper claims that a theoretically sound boundary can be drawnbetween semantical and pragmatical approaches if we look at the waythey deliver interpretations. Semantic interpretations are typically the resultof some kind of calculus, whereas pragmatic interpretations are typicallythe result of some working out where no calculus intervenes, rather ahighly specific solution is sought in order to integrate some unexpectedfact into a coherent story. Thus defined, Semantics and Pragmatics can bereferred to as deduction and abduction, respectively.In the light of the distinction just described, I revisit some of the phenomenathat were pointed out in the last decades as best examples of the pragmaticfunctioning of natural language. I argue that presupposition, deixis andspeech acts, highly predictable from lexicon and grammar, are semanticalin nature; on the contrary, implicature, since it depends on abductivethinking and it is not predictable from linguistic form, is described as apragmatic phenomenon par excellence.